540A simulation to evaluate HTLV-1 screening for pregnant women in prevention of adult T-cell leukemia. (2nd September 2021) - Tomoya, Takiguchi; Nishino, Yoshikazu; Fukui, Keisuke; Koriyama, Chihaya; Itabashi, Kazuo
Abstract: Background: In Japan, the nation-wide screening program of pregnant women for HTLV-1 infection was launched in 2010 to prevent mother-to-child transmission. It is difficult to assess the effect of the screening program on adult T-cell leukemia (ATL) prevention by observational study because ATL develops after long-term (about 50 years) latency in HTLV-1 carriers. Thus, we assessed the effect of the screening using computer simulation. Methods: We constructed our model that simulates lifetime history of the children born to HTLV-1 carrier mothers. Lifetime risks of ATL among the children in unscreened group and screened group were estimated employing Monte Carlo simulation. We developed three scenarios for the risk estimation of ATL in screened groups, each making different assumptions for the choice of feeding methods (formula feeding, short-term breast-feeding, and long-term breast-feeding). Results: Our simulation revealed that lifetime risk of ATL among the children born to HTLV-1 carrier mothers was 1.19 % in unscreened group and 0.21 to 0.27 % in screened groups. Conclusions: In Japan, it is estimated that there were 1, 363 pregnant women with HTLV-1 infection in 2016 (Sekizawa 2018). From this figure, the estimated annual number of ATL patients prevented by the screening is 12.6 to 13.5. Key message: HTLV-1 screening in pregnant women for one year is estimated to reduce the number of ATL among their children by about 13 in Japan.